The Impact of Physical Exercise on Motor Education to Pupils - Bozaxhiu, Arben; Dako, Natasha; Bano, Elton; Ikonomi, Edison; Agalliu, Artan (Arena-Journal of Physical Activities, 2023)
Introduction: Physical exercise, as an application of body exercises, is an adapted process, which during the application of movement activities causes changes in human abilities, from the initial ones to the desired ones. Physical exercise is an adapted, thought-out and organized process with the application of certain exercises and methods, which cause changes in the exerciser’s physical condition. The purpose of this paper review is to analyze the literature and understand every movement or every physical activity that in a correct and harmonious manner with legalities, is carried out for the achievement of concrete actions of physical education. In fact, it has an important impact on physical exercise is: - creation of certain skills and habits; - development and improvement of movement and functional skills; - satisfaction of personality needs (creative, recreational and human needs, entertainment needs). Methodology: In order to fulfill this review are using methods of literature analysis, and is made combination and comparison of data from various works of authors varied. To successfully realize this review paper we studied and analyzed the contemporary scientific literature. The methods used are: literature analysis, physical activity and recommendations. Recommendations: In the literature used, one can clearly see the importance of understanding that, the higher quality level of pupil movement culture, the higher level of mastery of teaching tasks and the higher level of movement skills education.